The student loan mess : how good intentions created a trillion-dollar problem - Best, Joel; Best, Eric (Berkeley : University of California Press, 2014)
"Student loan debt in the U.S. now exceeds $1 trillion, more than the nation's credit-card debt. This timely book explains how and why student loans evolved, the concerns they've raised along the way, and how each policy designed to fix student loans winds up making things worse. The authors, a father and son team, provide an intergenerational, interdisciplinary approach to understanding how, over the last 70 years, Americans incrementally, with the best intentions, created our current student loan disaster. They examine the competing interests and shifting societal expectations that contributed to the problem, and offer recommendations for confronting the larger problem of college costs and student borrowing in the future"--
Includes bibliographical references and index.
Keywords: Student loans -- United States; Student loans -- Government policy -- United States; College graduates -- United States -- Finance, Personal; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Anthropology / Cultural